Using functional near-infrared spectroscopy to study word production in the brain: A picture-word interference study. (February 2021) - Hitomi, Toru; Gerrits, Robin; Hartsuiker, Robert J.
Abstract: This study assessed the usefulness of functional near-infrared spectroscopy (fNIRS) to study word production in the brain. As a test case, we focused on the semantic interference effect (SIE), which has been demonstrated in many behavioral studies and has also been studied using neuroimaging techniques. Experiment 1 examined whether fNIRS can identify neural correlates of the SIE in a cross-modal picture-word interference (PWI) paradigm. Native speakers of Flemish Dutch overtly named pictures in their first language (L1), while ignoring auditory distractor words either categorically related or unrelated to target names. Functional NIRS data were obtained from the bilateral frontal and temporal regions and analyzed with a general linear model. We observed the SIE in the naming latencies and fNIRS detected the SIE in the cortical language network including the inferior frontal gyrus, middle temporal gyrus, and precentral gyrus. Most areas showed a signal increase for the related condition compared with the unrelated condition. Experiment 2 tested whether fNIRS can pinpoint differences in neural activities related to semantic interference as a function of the target language in unbalanced bilinguals. Flemish Dutch-English unbalanced bilinguals therefore performed the same PWI task, but now with a second language (L2) naming condition as a separate block. We observed the SIE behaviorally in both language conditions; the size of the SIE was comparable in each language. FNIRS data indicated several channels showing different levels of sensitivity to the SIE between L1 and L2. Both experiments demonstrated that fNIRS could detect neural correlates of the SIE and target language. We will discuss the potential benefits and methodological concerns of using fNIRS for speech production research. Highlights: We aim at evaluating the usefulness of fNIRS in speech production research. FNIRS can detect cortical regions sensitive to the semantic interference effect (SIE). FNIRS shows distinct activation patterns to SIE in L1 and in L2. FNIRS is a useful neuroimaging tool to study speech production in the brain.